Challenging Patriarchal Readings of Nusyuz: A Maqāṣid al-Sharī‘ah Approach to Strengthening Women’s Legal Safeguards - Wati, Rahmatul Lidia; Rizkyta, Danisha Nashwa; Nadhifa, Azkiya Wafiq; Fadhilah, Nur (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This study examines the reconstruction of nusyuz through the framework of maqāṣid al-sharī‘ah in response to domestic violence against women in Indonesia. The research addresses three questions: how nusyuz is defined in classical fiqh and Indonesian statutory law, which Islamic legal principles support women’s right to safety and resistance to harm, and how maqāṣid al-sharī‘ah can be operationalized to produce a more just interpretation. Employing a normative legal research method, the study is based on qualitative library research. Data were obtained from primary legal sources, including classical fiqh texts, Qur’anic exegesis of QS 4:34, and Indonesian family law regulations—particularly the Kompilasi Hukum Islam—as well as secondary sources such as peer-reviewed journal articles on domestic violence, gender justice, and Islamic legal reform. The analysis was conducted through three stages: doctrinal analysis to map prevailing definitions of nusyuz; contextual-hermeneutical analysis to relate these doctrines to Indonesian socio-legal realities and judicial practices; and maqāṣid-based evaluation using ḥifẓ al-nafs, protection of dignity, and the principle of dar’ al-mafāsid as analytical benchmarks. The findings show that classical and statutory constructions of nusyuz are often shaped by patriarchal assumptions and inadequately distinguish disobedience from self-protection. This study concludes that acts undertaken by wives to protect themselves from harm cannot be classified as nusyuz, and that marital obligations must be understood as reciprocal. By operationalizing maqāṣid al-sharī‘ah as an analytical tool, this research offers a context-sensitive and doctrinally grounded framework for strengthening women’s legal safeguards in Islamic family law.